Capillary pruning couples tissue perfusion and oxygenation with cardiomyocyte maturation in the postnatal mouse heart - Santamaría, Ricardo; Cruz-Caballero, Javier; Gkontra, Polyxeni; Jiménez-Montiel, Alberto; Clemente, Cristina; López, Juan A.; Villalba-Orero, María; Vázquez, Jesús; Hutloff, Andreas; Lara-Pezzi, Enrique; Arroyo, Alicia G. (Frontiers in Cell and Developmental Biology, 2023)
Removal of poorly perfused capillaries by pruning contributes to remodeling the microvasculature to optimize oxygen and nutrient delivery. Blood flow drives this process by promoting the intravascular migration of endothelial cells in developing networks, such as in the yolk sac, zebrafish brain or postnatal mouse retina. In this study, we have implemented innovative tools to recognize capillary pruning in the complex 3D coronary microvasculature of the postnatal mouse heart. We have also experimentally tested the impact of decreasing pruning on the structure and function of this network by altering blood flow with two different vasodilators: losartan and prazosin. Although both drugs reduced capillary pruning, a combination of experiments based on ex vivo imaging, proteomics, electron microscopy and in vivo functional approaches showed that losartan treatment resulted in an inefficient coronary network, reduced myocardial oxygenation and metabolic changes that delayed the arrest of cardiomyocyte proliferation, in contrast to the effects of prazosin, probably due to its concomitant promotion of capillary expansion. Our work demonstrates that capillary pruning contributes to proper maturation and function of the heart and that manipulation of blood flow may be a novel strategy to refine the microvasculature and improve tissue perfusion after damage.